Performance of students’ with Learning Disabilities (LD) on Ravens’ coloured progressive Matrices - Shazia Iqbal Hashmi; Getrude C. Ah Gang @ Grace; Chua, Bee Seok (Southeast Asia Psychology Journal, 2016)
The main objective of the present study was to explore the performance of students with learning disabilities on test of intellectual functioning. Apart from that, this study also focused on observing the difference in intellectual abilities among male and female students with learning disabilities as well. The participants were 80 students within the age ranges of 8- 11 years old; which consist of 47 males and 33 females diagnosed as having learning disabilities from five public schools in Kota Kinabalu, Sabah Malaysia. Raven’s Coloured Progressive Matrices (Raven, 1995) was used to assess students’ intellectual functioning. It was found that the performance of 12.5% children were on intellectually superior level, 38.5% were on definitely above average, 22.5% were on average, 11.3 % were below average, and 15% were on intellectually impaired level. As for gender difference in scores, the results of non-parametric Fisher Exact test showed that significant association between gender and children intellectual ability ( =18.94, df = 4, p < .05) was found. On the basis of observed cell frequencies, it can be concluded that male students’ performance was more towards the extreme of higher and lower ends and female students’ performance was more towards average. The differences in basic intellectual abilities determined during the present study can be used as a guideline by the responsible authorities to identify appropriate and individualized interventions which are suitable for different group of children based on their level of intellectual functioning and learning disabilities.